Detecting Ultralow Frequency Mutation in Circulating Cell‐Free DNA of Early‐Stage Nonsmall Cell Lung Cancer Patients with Unique Molecular Identifiers. Issue 10 (26th April 2019) - Yang, Yang; Zheng, Di; Wu, Chunyan; Lizaso, Analyn; Ye, Junyi; Chuai, Shannon; Ni, Jian; Xu, Jianfang; Jiang, Gening
Abstract: The performance of next generation sequencing in profiling somatic mutations from plasma samples, especially in early‐stage cancer, is limited by its sensitivity due to the extremely low amount of cell‐free DNA (cfDNA). Polymerase‐chain reaction amplification of limited amounts of DNA often results in product redundancy and the amplification of contaminant DNA. Numerous methods have been developed to detect and quantify ultralow frequency mutations. In this study, the potential of tagging each DNA molecule with a unique molecular identifier (UMI) is explored to detect ultralow frequency mutations in early‐stage lung cancer patients. Paired tissue and blood samples from 32 patients with early‐stage (stage IA‐IIB) nonsmall cell lung cancer are sequenced using a panel consisting of 168 cancer‐related genes. Collectively, 93.8% of tissue samples and 59.4% of plasma samples have mutations detected. The concordance rates are acceptable for all patients except for stage IA. Notably, mutations at an alleleic frequency as low as 0.1% are detected in UMI‐tagged cfDNA samples. Moreover, patients with nonadenocarcinoma histology have a significantly higher detection rate than patients with adenocarcinoma (92.9% vs 33.3%, P = 0.002). The study demonstrates the potential of UMI in early detection of lung cancer from plasma samples. Abstract : The replacement of standard adapters with UMIs in the capture‐based targeted next‐generation sequencing workflow allow the accurate detection of ultralow frequency mutations in circulating cell‐free DNA derived from the blood of early lung cancer patients.